GAMBARAN PENYESUAIAN PSIKOLOGIS PADA INDIVIDU PASCA CEDERA OTAK: A SCOPING REVIEW - Nabella, Abigail; Mukhlina, Nova; Syifa Paramitha Divani, Prajna; Jauza, Nabila; Amira Mulika, Rifda; Khakim, Zulfikri; Wimbarti, Supra (Judika (Jurnal Nusantara Medika), 2024)
This scoping review explores the psychological adjustment of individuals after brain injuries, focusing on its impact on cognitive, emotional, and social functions, as well as the factors that influence recovery. Relevant literature was sourced from databases like PubMed and Google Scholar using search terms such as “acquired brain injury,” "traumatic brain injury," "psychological adjustment," "quality of life," and "psychological adaptation." Only empirical studies published between 2019 and 2024 in English were included. The review identified several studies highlighting that brain injuries result in significant cognitive, emotional, and functional impairments. Factors influencing recovery include internal aspects such as resilience and self-efficacy, and external factors like social support and rehabilitation access. Studies also indicated a correlation between positive psychological adjustment and improved life satisfaction and functional independence. Our findings emphasize the importance of interventions that focus on emotional regulation, social support, and realistic goal-setting to improve recovery and quality of life. Further research is recommended to explore specific strategies that enhance psychological adjustment in TBI survivors.